2010
DOI: 10.1088/0031-9155/55/4/022
|View full text |Cite
|
Sign up to set email alerts
|

IMRT for the breast: a comparison of tangential planning techniques

Abstract: Three intensity-modulated tangential beam radiotherapy plan types for breast cancer treatment were evaluated based on PTV homogeneity index (HI) and equivalent uniform dose (EUD), heart V30 and EUD, whole lung V20 and EUD, and typical planning time compared to conventional 2D plans. 20 early-stage breast cancer patients were CT-scanned in the supine position, and tangential field extent, gantry and collimator angles were chosen. Four treatment plans were created for each patient: conventional, dynamically wedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
(35 reference statements)
3
36
0
Order By: Relevance
“…In agreement with the literature, comparison of calculated plan parameters showed an advantage of TB-IMRT compared to 3D-CRT concerning the CI, heart dose in patients with left-sided breast cancer and ipsilateral lung dose [6,7,21]. As expected, due to the multiple beam angles used, 7 F-IMRT showed a higher low-dose volume to the heart, ipsilateral and contralateral lung compared to TB-IMRT [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with the literature, comparison of calculated plan parameters showed an advantage of TB-IMRT compared to 3D-CRT concerning the CI, heart dose in patients with left-sided breast cancer and ipsilateral lung dose [6,7,21]. As expected, due to the multiple beam angles used, 7 F-IMRT showed a higher low-dose volume to the heart, ipsilateral and contralateral lung compared to TB-IMRT [22].…”
Section: Discussionsupporting
confidence: 85%
“…Intensity modulated radiotherapy (IMRT) has the potential to improve dose homogeneity and conformity of a radiotherapy of the breast or chest wall thereby reducing side-effects [4-7]. Concerning skin toxicity, several studies have reported clinical benefit for IMRT of the breast [8-12].…”
Section: Introductionmentioning
confidence: 99%
“…10 The development of accelerators with multi-leaf collimators (MLC) has facilitated the creation of newer techniques, such as field-in-field intensity-modulated RT (FiF-IMRT). 11,12 In this clinic, 3D-CRT is used as the routine planning technique for treating the intact breast. However, two major questions are raised.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that IMRT requires longer planning time and advanced planning skills 32. Smith et al32 found that CRT required a mean time of 15 minutes compared to 60–90 minutes required by FP FIF IMRT, while Al-Rahbi et al15 reported an average time of 20–30 minutes, 15–20 minutes, and 45–60 minutes for 3D CRT, FP FIF IMRT, and IP IMRT, respectively.…”
Section: Types Of Breast Imrt Techniquesmentioning
confidence: 99%
“…Smith et al32 found that CRT required a mean time of 15 minutes compared to 60–90 minutes required by FP FIF IMRT, while Al-Rahbi et al15 reported an average time of 20–30 minutes, 15–20 minutes, and 45–60 minutes for 3D CRT, FP FIF IMRT, and IP IMRT, respectively. It is interesting to note that the planning time for FP FIF IMRT is quartered in Al-Rahbi et al’s15 study.…”
Section: Types Of Breast Imrt Techniquesmentioning
confidence: 99%